Whistler waves shown to disappear close to the Sun. (1st August 2022) - Dumé, Isabelle
Abstract : An analysis of data from NASA's Parker Solar Probe has revealed that electromagnetic "whistler waves" are unexpectedly absent from certain regions of the Sun's upper atmosphere.